Linking academic self-initiated expatriate's cultural intelligence to specific job outcomes: The enabling role of psychological capital - Abdulrasheed Abdullah Aminullah; Asniza Yusuf; Farah Lina Azizan; Isyaku Salisu; Zulkafli Bin Mansor (Cogent Business & Management, 2022)
Several data-driven investigations studies examined the association between cultural intelligence and job outcomes (intention to stay, Work performance and organisational citizenship behaviour). It is, however, surprising that the moderating role of psychological capital hasn't been previously examined concerning cultural intelligence and job outcomes. This relationship is therefore currently under-researched due to sparse contributions. This research investigates psychological capital potential moderating role in the relationship between cultural intelligence and job outcomes to address this gap in the organisation's literature. Due to this context, the study's purpose is to support this hypothesis in the data collected from a sample of 246 self-initiated studies on expatriates in 20 Malaysian public universities. Relying on a quantitative method and using Partial Least Squares structural equation modelling to analyse the data, the results reveal that cultural intelligence predicted all three components of job outcomes. Additionally, psychological capital moderates the relationship between cultural intelligence and work performance so that when positive psychological capital is high, the association is more robust. The study has contributed by offering a context-bound approach to refine and integrate the social exchange theory with self-initiated academic expatriates' cognitive, affective and behavioral processes in the Malaysian situation. Unlike previous studies of working abroad, this study indicates that cultural intelligence can be a salient personal resource for self-initiated expatriates' academics working in a foreign environment. Theoretical and practical implications are discussed based on the findings of this research.
Keywords: 650; Cultural intelligence; intention to remain and work performance; job outcomes; organizational citizenship behavior; psychological capital